In vitro study on the antifungal effect of the ethanolic extract of malunggay (Moringa oleifera) leaves against Candida albicans/Joachim Christian M. Diva, Jillianne A. Santos, and Monica Gayle C. Tan. - Diva, Joachim Christian M. Author; Santos, Jillianne A. Author; Tan, Monica Gayle C. Author; Lachica, Marie Rossini Carmela T. (2023)
INTRODUCTION: Candida albicans is a commensal organism typically found in healthy adults. However, it can become opportunistic and lead to conditions due to an imbalance in the normal microflora. among these conditions, is candidiasis, a prominent fungal infection in the Philippines, and a notable manifestation of this is seen in the mouth, commonly known as oral thrush. While pharmacological medications are available, this study aims to determine the presence and potency of Moringa oleifera leaves ethanolic extracts against C. albicans.
METHODS: Previous studies using Moringa oleifera leaves showed an inhibitive effect on C> albicans. In this study, ethanolic extracts of M. oleifera leaves were used to determine their antifungal properties, in vitro. the extracts had varying concentrations of 50 mg/ml, 75 mg/ml, 100mg/ml and 125 mg/ml. Antifungal properties were determined using the disk diffusion method. After 24 hours of incubation, the zones of inhibition were observed and measured. The experiment was done in three triplicates.
RESULTS: Contrary to published reports using extracts of M. oleifera leaves, all ethanolic extract concentrations of M. oleifera leaves showed no zone of inhibition. Only the positive control, clotrimazole, produced inhibition zones with an average of 16.04 mm.
CONCLUSION: The study concludes that the effect of the ethanolic extracts of M. oleifera leaves on C. albicans is similar to that of the negative control, in vitro.
Seminar Paper--Doctor of Dental Medicine--University of the Philippines Manila.
Keywords: Candida albicans; Moringa Oleifera; Candidiasis